A comparison of chiral separations by supercritical fluid chromatography and high-performance liquid chromatography. Issue 11 (21st July 2021) - Ali, Imran; Raja, Rupak; Alam, Syed Dilshad; Shirsath, Vikas; K. Jain, Arvind; Locatelli, Marcello; David, Victor
Abstract: The supercritical fluid chromatography technique is one of the most promising and innovative technologies used in the analysis as well as the separation of various racemates. The various enantiomers have been separated using SFC due to its several merits over conventional HPLC methods such as low cost, wide polarity compatibility, higher column efficiency, and fast analyzing capability, which are desirable features for the pharmaceutical industry. Therefore, it was considered worthwhile to review the applications of SFC in achiral and chiral separations. This review encompasses the latest literature exploration of various practical aspects of SFC for enantiomeric separation, purification, and applications to the pharmaceutical industry. A detailed discussion of SFC was made in terms of productivity, stacked injections, sample solubility, particle size, green incentive, organic solvent, recycle solvents, and economical aspects. Besides, future perspectives of SFC have also been highlighted. A comparison was also made between SFC and HPLC. SFC has been found better technique than HPLC for the chiral separations on a preparative scale. This article will be highly useful for chiral chromatography in pharmaceutical industries and research laboratories. Graphical Abstract: UF0001